A Case Study Analysis of Separation Anxiety in Early Childhood in Twins - Stiliyana Stamova (The Global Psychotherapist)
It should be borne in mind that twins often experience a double dependence on both their parents and their twin. Children show considerable individual attachment to their parents, and the study sought to highlight the importance of personality structure and social environment in influencing anxiety responses in children. Positive psychotherapy was chosen as the method of working in both situations, and tools designed to promote the development of internal coping strategies were applied. The paper proposes a model for possible therapeutic work with twins at risk of anxiety disorders, suggesting that an empathic therapeutic approach may be useful in reducing separation anxiety in infancy.